Impact of subclinical mastitis on milk yield and economic return of dairy cows - Gonçalves, Juliano Leonel (2017)
The general objectives of the present thesis were to evaluate: (i) the effects of subclinical mastitis (SM) caused by major pathogens on SCC, milk leukocyte differentials (MLD) and milk yield; (ii) milk yield losses caused by SM at the cow and quarter level; and (iii) the economic impact of SM caused by major pathogens. The thesis was structured in four studies. In study 1, quarter milk samples (n = 302) from 78 cows with SCC gt;200,000 cells/mL were analyzed by milk leukocyte differential (MLD) methodology and by microbiological culture (MC). Quarters with positive-culture results were obtained from 102/156 (65.4%) of MLD-positive milk samples, while 28/135 (20.7%) of MLD-negative milk samples were MC-positive. When MC was considered the gold standard for mastitis diagnosis, the sensitivity (Se) of the MLD was 65.4% (IC95% = 57.4 to 72.8%) and the specificity (Sp) was 79.3% (IC95% = 71.4% to 85.7%). In conclusion, the use of the MLD on cows with monthly composite SCC > 200×103 cells/mL for screening at quarter level identified quarters more likely to be culture-positive. In study 2, the effect of different pathogens was evaluated by comparison of contralateral (healthy and infected) mammary quarters of 146 lactating cows. The impact of SM on economic return (quarter milk yield × milk price) was determined by applying milk payment estimates on milk collected from healthy versus infected glands. The milk losses ranged from 0.07 Kg/quarter.milking to 2.9 Kg/quarter.milking, and varied according to the pathogen causing SM. Economic losses were higher for SM caused by Enterococcus spp. (US$0.43/quarter.milking), Strep. Dysgalactiae (US$ 0.74/quarter.milking) and E. coli (US$0.98/quarter.milking). Additionally, there was a trend for Staph. aureus and Citrobacter spp. To induce economic losses of US$ 0.26 and 0.29/quarter.milking, respectively. In general, the economic return was lower in quarters with SM caused by environmental and contagious pathogens (US$ 0.18 and 0.22/quarter.milking, respectively) when compared to their healthy contralateral quarters. In study 3, a total of 146 out of 650 lactating cows were selected from seven dairy herds for having composite milk SCC > 200,000 cells/mL in combination with the isolation of a major mastitis pathogen. From these selected cows, 1,436 quarter milk samples were collected during three successive sampling occasions at intervals of 15-20 days. Quarter milk yield was measured by milking the mammary quarters individually using three successive milk samplings over time. Bacterial isolates were identified by microbiological culture, MALDI-TOF MS and partial sequencing of the 16S rRNA gene. Milk losses and economic returns varied according to the type of mastitis-causing pathogen: 0.24 to -0.87 kg/quarter.milking for environmental streptococci, and -1.57 to -1.69 kg/quarter.milking for Staph. aureus. Overall, mammary quarters that were cured from SM caused by Staph. aureus and environmental streptococci exhibited an increase in economic return of approximately 0.47 and 0.69 US$/quarter.milking, respectively. In study 4, test day records (n = 1,200,002) were obtained from the Paraná State Holstein Association, which included data from 92,560 lactating cows, from 781 herds, from January 2010 to December 2015. A segmented regression was fitted to estimate the cut-off point of Log10SCC scale where milk yield started to be affected by mastitis: 0.90 (~7,963 cells/mL). In conclusion, first lactation cows have a reduction of 1.37 to 2.28 kg/cow/d of milk yield for each increase of one unit of Log10SCC over the cutoff point, whereas second and later lactation cows are expected to have milk yield losses of 2.36 to 4.20 kg/cow/d for each unit increase of Log10SCC over the cutoff point. Overall, the results of this thesis indicated that milk losses depend on the type of pathogen causing SM. Major pathogens have showed greater effects on milk quality than when it was observed using the approach of culture results of negative or positive. The methodology for evaluation of subclinical mastitis effect on milk yield interferes in the estimation of milk losses, and should include factors such as DIM and number of parity.